Vitamin D and Lung Cancer Risk: A Comprehensive Review and Meta-Analysis - Liqun Zhang; Sihai Wang; Xiaoyu Che; Xuehui Li (Cellular Physiology and Biochemistry, 2015)
Background/Aim: Vitamin D has been suggested to have important roles against cancer development. There were several published studies on the association between vitamin D and lung cancer risk, but not conclusive results were available. Methods: To clarify the role of vitamin D in lung carcinogenesis, we performed a comprehensive review of the literature and a meta-analysis to evaluate the association of serum vitamin D levels and dietary vitamin D intake with lung cancer risk. Twelve studies (9 prospective cohort and 3 nested case-control studies) with a total of 288,778 individuals were included. The summary relative risk (RR) with 95% confidence interval (CI) was used to assess lung cancer risk. Results: Meta-analysis of total 12 studies showed that RR for the association of high vitamin D status with lung cancer was 0.84 (95%CI 0.78-0.90, P Conclusion: Current data suggest an inverse association between serum vitamin D and lung cancer risk. Further studies are needed to investigate the effect of vitamin D intake on lung cancer risk and to evaluate whether vitamin D supplementation can prevent lung cancer.